1982
DOI: 10.1073/pnas.79.9.2803
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of rat insulins I and II: evidence for differential expression of the two genes.

Abstract: The purpose of these experiments was to determine the relative content and biosynthetic rate of insulins I and II under various experimental conditions. The two insulins were quantitated by polyacrylamide gel electrophoresis, electrotransfer to nitrocellulose paper, photoaffinity crosslinking, and immunodetection with anti-insulin antibody and '5I-labeled protein A. The ratio (mean ± SEM) of insulins, I/HI, was 1.2 ± 0.2 in Wistar-Furth rats fasted for 4 days, 1.6 ± 0.2 in normal rats, and 5.5 ± 0.8 in growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
(34 reference statements)
1
19
0
2
Order By: Relevance
“…We have revealed that MafA activates the rat insulin promoter II, but not promoter I. It has been reported that the responses of rat insulin genes to stimulation are different [33,34]. Our results imply that, under conditions of stimulation, the difference between rat insulin promoters I and II depends on Maf regulation.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…We have revealed that MafA activates the rat insulin promoter II, but not promoter I. It has been reported that the responses of rat insulin genes to stimulation are different [33,34]. Our results imply that, under conditions of stimulation, the difference between rat insulin promoters I and II depends on Maf regulation.…”
Section: Discussionsupporting
confidence: 47%
“…In this study, we indicated that MafA and MafB activate the RIPII and bind to the core site of RIPE3b. Mouse and rat possess two insulin promoters each (insulin promoters I and II), whereas human possesses only one promoter; these insulin promoters have unique transcriptional regulations [33][34][35][36]. Two significant differences appeared when the RIPE3b sequences of these insulin promoters were aligned with the MARE sequence (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat I insulin contains no methionine, but there is a substitution of a lysine for a methionine at residue 29 of the rat insulin II B-chain [2,15]. The use of [35S]methionine instead of [3H]leucine in the pulse-labelling period therefore allows for monitoring of only rat insulin II biosynthesis.…”
Section: Methodsmentioning
confidence: 99%
“…However, the issue of Correspondence address: P.A. Halban, Joslin Diabetes Center, 1 Joslin Place, Boston, MA 02215, USA whether glucose regulates the synthesis of both rat insulins I and II, although addressed, has remained unresolved due to inadequate resolution of rat insulin I from proinsulins and the non-quantitative transfer to nitrocellulose of rat insulin II with the immunoelectrophoretic system used [15][16][17]. To avoid such analytical problems, we have used highperformance liquid chromatography (HPLC) to monitor glucose stimulation of rat insulin I and II biosynthesis in isolated islets.…”
Section: Introductionmentioning
confidence: 99%